Development of the foundations of a new agricultural policy of the Russian empire the special meeting the needs of agricultural industry - Svyaschenko, Zinaida (Skhid, 2013)
The article attempts by analyzing the source base to explore the development of the foundations of a new agricultural policy of the Russian Empire beginning of the twentieth century The special meeting of the needs of the agricultural industry. The attention to the problem of the fate of the peasant communities and peasant management reform.